2010
DOI: 10.1371/journal.pone.0015401
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Dopamine Is Critical for Pattern Completion during Associative Memory Recall

Abstract: Pattern completion, the ability to retrieve complete memories initiated by partial cues, is a critical feature of the memory process. However, little is known regarding the molecular and cellular mechanisms underlying this process. To study the role of dopamine in memory recall, we have analyzed dopamine transporter heterozygous knockout mice (DAT+/−), and found that while these mice possess normal learning, consolidation, and memory recall under full cue conditions, they exhibit specific deficits in pattern c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 46 publications
0
27
1
Order By: Relevance
“…In addition, these heterozygous mice showed an increase in the exploration of objects placed in an open field [17], and in the frequency of object exploration [20]. DAT +/− mice showed impaired pattern completion in an environment with few spatial cues, which could be reversed by haloperidol [19]. However, no impairment of OR has been described [19,20].…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, these heterozygous mice showed an increase in the exploration of objects placed in an open field [17], and in the frequency of object exploration [20]. DAT +/− mice showed impaired pattern completion in an environment with few spatial cues, which could be reversed by haloperidol [19]. However, no impairment of OR has been described [19,20].…”
mentioning
confidence: 98%
“…Previous studies revealed that DAT +/− mice show impairment in pattern completion in a partial cue environment [19], and exhibit decreased anxiety-related behaviors [20]. The mild hyperdopaminergic DAT +/− mice present biochemical changes [18] related to memory impairment that could be reversed by D2 down regulation [19].…”
mentioning
confidence: 98%
See 3 more Smart Citations